Mathematics and chemical kinetics and engineering - Marin, Guy B.; West, D. H.; Yablonsky, Gregory (Advances in chemical engineering ;, 2008)
The cross-fertilization of physico-chemical and mathematical ideas has a long historical tradition. This volume of Advances in Chemical Engineering is almost completely dedicated to a conference on "Mathematics in Chemical Kinetics and Engineering" (MaCKiE-2007) which was held in Houston in February 2007, bringing together about 40 mathematicians, chemists, and chemical engineers from ten countries to discuss the application and development of mathematical tools in their respective fields. * Updates and informs the reader on the latest research findings using original reviews * Written by leading industry experts and scholars * Reviews and analyses developments in the field.